2004
DOI: 10.1364/ao.43.001533
|View full text |Cite
|
Sign up to set email alerts
|

Volume holographic imaging in transmission geometry

Abstract: We address the performance of transmission geometry volume holograms as depth-selective imaging elements. We consider two simple implementations using holograms recorded with spherical and plane beams. We derive the point-spread function (PSF) of these systems using volume diffraction theory and use the PSF to estimate depth resolution. Furthermore, we show that appropriately designed objective optics can significantly improve the depth resolution or the working distance of plane-wave reference holographic ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…We examine two common VHs [10,11] in detail. For simplicity, the lateral dimension of VHs is assumed to be infinitely extended.…”
Section: Examplesmentioning
confidence: 99%
“…We examine two common VHs [10,11] in detail. For simplicity, the lateral dimension of VHs is assumed to be infinitely extended.…”
Section: Examplesmentioning
confidence: 99%
“…We have previously 24 derived the impulse response as a function of axial defocus for both SR-and PR-VHI systems. Figure 3͑a͒ is a schematic of a SR-VHI system.…”
Section: Vhi Implementationsmentioning
confidence: 99%
“…͑3͒ and ͑4͒ is because the SR-VHI system images objects in the Fresnel diffraction regime, whereas the PR-VHI system images objects in the Fraunhofer ͑on account of the collimating lens͒ diffraction regime. 24 This leads to interesting problems while designing the appropriate objective optics for the VHI system, and we have shown that the inverse linear dependence on aperture size of PR-VHI can be exploited to achieve optimal depth resolution at a particular working distance. 24 VHI systems in several of the subcategories mentioned in Sec.…”
Section: ͑2͒mentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 It is a significant source of concern in application areas such as holographic memories, 8,9 information processing, 10 interconnects, 11 and imaging applications. 12 For example, researchers have investigated polymer materials with minimal shrinkage [13][14][15][16] and methods to compensate the deviation due to shrinkage. 17,18 Based on shrinkage only, the models used in the literature are relatively simple, treating linear deformation only.…”
Section: Introductionmentioning
confidence: 99%